تكوين البيئة اللغوية على ضوء المدخل الإتصالي في معهد دار السلام جومبانج: The Formation of The Arabic Language Environment Based on Communicative Approach At Darussalam Islamic Boarding School Jombang - Naufal Fachri Mubarok (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This research aims to: 1) Describe the process of establishing a language environment at Darussalam Islamic Boarding School Jombang in terms of the Communicative Approach. 2) Describe the facilitating factors and inhibiting factors in the establishment of a language environment at Darussalam Islamic Boarding School Jombang from the perspective of the Communicative Approach. The researcher used a qualitative research method, specifically the descriptive type. This is because the data required is in the form of detailed information related to the scope of the research. The data collection instruments used in this study were interviews, observations, and documentation. We are conducting an interview with seven people, including: the deputy manager, the institute professor, the institute administrator, and four students from the tenth and eleventh grades. The research findings are as follows: 1) The process of establishing a language environment in Darussalam Islamic Boarding School Jombang, as viewed from the Communicative Approach, includes requiring students to use Arabic in formal education and daily activities. conducting activities to enhance Arabic language skills for both students and teachers. Various language-related activities are organized, such as Muhadatsah, Idhof, Muhadhoroh, Ayyamul Lugha, and Masrohiyyah. 2) The factors that encourage the establishment of a language environment in Darussalam Islamic Boarding School Jombang, as viewed from the Communicative Approach, include the correlation between the pesantren and schools, the use of communicative approach in teaching and daily conversations, and the use of materials tailored to the needs of students and the good communicative competence of pesantren teachers. The factors that hinder the establishment of a language environment in Darussalam Islamic Boarding School Jombang, as viewed from the Communicative Approach, include the high intensity of English language usage, the weak Arabic language skills of some pesantren administrators, the weak Arabic language skills of some school teachers, and the lack of confidence among students in speaking Arabic.